Genesis 1-11 - Gertz, Jan Christian (Historical commentary on the Old Testament, 2023)
Genesis 1-11 considers the origins of the world and how it is ordered, the origin of humanity and the origins of civilization. It is an expression of the basic conviction, widespread in antiquity, that everything present and everything future received its essence in the beginning. In this sense, the biblical Primeval History is less an explanation of the origin of the world than primarily an atempt to understand humanity's experience with itself and its environment in an interpretive way. At the center of this reflection in exemplary narratives, in addition to natural history, genealogy and geography, is humanity in its manifold relationships with its fellow humanity, with non-human Creation, and with God. The commentary offers readers inside and outside the field a clearly understandable synthesis of previous research and places the Primeval History within the context of the literature of the ancient Near East